The corporate transformation of health care : can the public interest still be served? - Geyman, John P., 1931- (Springer Pub. Co., 2004)
Annotation The author explores how the corporate transformation of hospitals, HMOs, and the insurance and pharmaceutical industries has resulted in reduction in services, dangerous cost cutting, poor regulation, and corrupt research. He sheds light on the political lobbying and media manipulation that keeps the present system in place. Exposing the shortcomings of reform proposals that do little to alter the status quo, he makes a case for a workable single-payer system. This is an essential read for today's practitioners, policy makers, healthcare analysts and providers, and all those concerned with the precarious state of America's under- and uninsured.